2008
DOI: 10.1158/0008-5472.can-07-3086
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Receptor A as a Novel Anticancer Target

Abstract: The receptor for atrial natriuretic peptide (ANP), natriuretic peptide receptor A (NPRA), is expressed in cancer cells, and natriuretic peptides have been implicated in cancers. However, the direct role of NPRA signaling in tumorigenesis remains elusive. Here, we report that NPRA expression and signaling is important for tumor growth. NPRA-deficient mice showed significantly reduced antigen-induced pulmonary inflammation. NPRA deficiency also substantially protected C57BL/6 mice from lung, skin, and ovarian ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 43 publications
5
90
0
1
Order By: Relevance
“…Several studies have documented an antiproliferative effect of ANP in endothelial cells as well as in different types of cancer cells (15)(16)(17)(18)(19)(20)(21). Indeed, it has been proposed that ANP counteracts tumorigenesis through feedback inhibition of its receptor, natriuretic peptide receptor A, that seems to drive tumor angiogenesis through VEGF induction (49). Moreover, endothelin-1-and VEGFdependent angiogenesis were inhibited by ANP (15,18,19), suggesting that ANP has opposing effects on some of the angiogenic signaling pathways triggered by ADM and vasopressin.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented an antiproliferative effect of ANP in endothelial cells as well as in different types of cancer cells (15)(16)(17)(18)(19)(20)(21). Indeed, it has been proposed that ANP counteracts tumorigenesis through feedback inhibition of its receptor, natriuretic peptide receptor A, that seems to drive tumor angiogenesis through VEGF induction (49). Moreover, endothelin-1-and VEGFdependent angiogenesis were inhibited by ANP (15,18,19), suggesting that ANP has opposing effects on some of the angiogenic signaling pathways triggered by ADM and vasopressin.…”
Section: Discussionmentioning
confidence: 99%
“…Side population Szotek et al [9] CD44/CD117 Zhang et al [10] Natriureticpeptide receptor A Kong et al [11] CD133 Ferradina et al [45] CD24 Gao et al [13] DEAD box polypeptide 4 Hashimoto et al [12] expressed DDX4 whereas the CD133-negative cells did not. The genetic program regulating the self-renewal and differentiation of CSCs plays a key role in cancer initiation, invasion and migration.…”
Section: Ovarian Cancer Stem Cells: Is There Any Relationship Betweenmentioning
confidence: 99%
“…In 2004, Johnson et al [1] demonstrated the existence of proliferative GSCs in the ovaries of adult mice, and recently, ovarian GSCs have been isolated and characterized in the ovaries of postnatal mice and reproductive-age women [7] . Amid the controversy created by Johnson et al [1] , the presence of cancer stem cells (CSC) in ovarian cancer was established by Bapat et al [8] , and accumulating data have provided substantial evidence for the involvement of CSCs in ovarian cancer [9][10][11][12][13] . Ovarian cancer (OC) is associated with enhanced tumor aggressiveness and metastasis, as well as drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…BNP-transgenic mice exhibit overgrowth of the growth-plate cartilage through a cGMPdependent mechanism . Furthermore, signaling through NPR-A plays a pivotal role in tumor growth (Kong et al, 2008). Although little is known about the role of NPs in pre-implantation embryo development, one study reported that NPR-B-deficient mice were sterile due to a lack of development of the reproductive system, and the majority (75%) of the NPR-B-deficient mice studied died before 100 days of age (Tamura et al, 2004).…”
Section: Introductionmentioning
confidence: 99%